2017
DOI: 10.1155/2017/5189803
|View full text |Cite
|
Sign up to set email alerts
|

Can Mitochondria DNA Provide a Novel Biomarker for Evaluating the Risk and Prognosis of Colorectal Cancer?

Abstract: Colorectal cancer (CRC) was one of the most frequent cancers worldwide. Accurate risk and prognosis evaluation could obtain better quality of life and longer survival time for the patients. Current research hotspot was focus on the gene biomarker to evaluate the risk and prognosis. Mitochondrion contains its own DNA and regulates self-replicating so that it can be as a candidate biomarker for evaluating the risk and prognosis of colorectal cancer. But there were already huge controversies on this issue. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 76 publications
0
15
0
Order By: Relevance
“…Recent data revealed that tumour cells of many types of cancer have fewer copies of mitochondrial DNA than the cells that make up normal tissue . On the other hand, mtDNA copies can be released into the circulation from damaged or disintegrating tumour cells and might result in a preponderance of mtDNA‐CN when these copies are measured only in cell‐free DNA . As we discussed recently , the measurement of mtDNA copy numbers from nuclear cells as done in our study is an attempt to assess relative mitochondrial abundance within cells, and therefore a higher mtDNA copy number is expected to be associated with beneficial outcomes as observed in the present study.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Recent data revealed that tumour cells of many types of cancer have fewer copies of mitochondrial DNA than the cells that make up normal tissue . On the other hand, mtDNA copies can be released into the circulation from damaged or disintegrating tumour cells and might result in a preponderance of mtDNA‐CN when these copies are measured only in cell‐free DNA . As we discussed recently , the measurement of mtDNA copy numbers from nuclear cells as done in our study is an attempt to assess relative mitochondrial abundance within cells, and therefore a higher mtDNA copy number is expected to be associated with beneficial outcomes as observed in the present study.…”
Section: Discussionmentioning
confidence: 64%
“…However, the risk was more than threefold increased in the lowest quartile of mtDNA‐CN. Currently, contrary information on the association between mtDNA‐CN and cancer can be found in the literature reporting decreased as well as increased mtDNA‐CN in patients with cancer . One of the reasons for these diverging results might be whether these measurements are done in the tumour tissue, peripheral blood mononuclear cells or whole blood or from cell‐free circulating mtDNA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 , 19 , 20 Multiple studies have indicated that some germline polymorphisms in mtDNA d-loop region may be related to an increased risk of the malignancies. 21 , 22 Cancer cells are very different from normal cells, and they use aerobic glycolysis, called warburg effect, to generate energy and metabolic intermediates for the rapid proliferation and aggressiveness. 23 A series of studies suggested that some pathogenic somatic mtDNA mutations of cancer cells can confer cancerogenesis, and promote aggressiveness in vitro and in vivo by changing mitochondrial metabolism, and activating anti-apoptotic and oncogenic signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Finally, mitochondria are the key location for carbohydrate metabolism, and mitochondrial dysfunction is one the most important features in colorectal cancer and intestinal flora imbalance. 31 , 32 …”
Section: Methodsmentioning
confidence: 99%